2016
DOI: 10.3389/fped.2016.00043
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for Implementation of Warm Cardiac Surgery in Pediatrics

Abstract: Cardiac surgery was developed thanks to the introduction of hypothermia and cardiopulmonary bypass in the early 1950s. The deep hypothermia protective effect has been essential to circulatory arrest complex cases repair. During the early times of open-heart surgery, a major concern was to decrease mortality and to improve short-term outcomes. Both mortality and morbidity dramatically decreased over a few decades. As a consequence, the drawbacks of deep hypothermia, with or without circulatory arrest, became mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 89 publications
0
1
0
1
Order By: Relevance
“…В этой экспериментальной работе показано, что уровень потребления кислорода гипотермически плегированного сердца пересекается с уровнем потребления пустого сокращающегося сердца: для первого потребление колеблется в диапазоне 0,7-2,8 мл кислорода на 100 г миокарда, для второго -1,5-5,0 мл. Теоретически остановленное сердце может потреблять такое же количество кислорода, как и пустое, сокращающееся при нормальной температуре сердце [52].…”
Section: защита миокардаunclassified
“…В этой экспериментальной работе показано, что уровень потребления кислорода гипотермически плегированного сердца пересекается с уровнем потребления пустого сокращающегося сердца: для первого потребление колеблется в диапазоне 0,7-2,8 мл кислорода на 100 г миокарда, для второго -1,5-5,0 мл. Теоретически остановленное сердце может потреблять такое же количество кислорода, как и пустое, сокращающееся при нормальной температуре сердце [52].…”
Section: защита миокардаunclassified
“…Higher release of endotoxin has been described with deep hypothermia [26]. There has been a trend to use less hypothermia in the field [49], without hard data to support this position. Schmitt et al showed that hypothermia increases the need for inotropic support but does not impact inflammation in children undergoing VSD closure [50].…”
Section: Temperature Of Perfusionmentioning
confidence: 99%